Erosion Rate Analysis and Land Conservation Direction Based on Geographic Information System in Way Rarem Subwatershed, Lampung Province - Napitupulu, Ruth Erditha; Andawayanti, Ussy; Lufira, Rahmah Dara; Pratama, Rizki Ramadhani (Fakultas Teknik Universitas Brawijaya, 2024)
The Ministry of Forestry has designated the Way Rarem sub-watershed, part of Tulang Bawang, a critical watershed, as a priority. Several reasons cause land criticality, including deforestation and inappropriate land use, which cause erosion and sedimentation. In this case, the criticality of the watershed occurs due to the high erosion rate, which impacts flooding in the Way Rarem subwatershed area. Over the past year, there have been flood disasters at five points in the Tulang Bawang watershed. Based on information from BNPB (National Disaster Management Agency), the flood disaster affected 140 families. The losses that occur due to flooding that arise due to erosion and sedimentation need to be studied in more depth; therefore, the situation in the Way Rarem Sub-watershed is important to study further. The objectives of this study are to determine the Erosion Hazard Index, measure the erosion rate in the Way Rarem sub-watershed using the USLE method, and provide adequate conservation strategies. The required data are rainfall data, soil type, slope, and land use in 2019 and 2023 as a comparison. GIS was used to process all the data. The results showed that the erosion rate in 2019 was 21933.9 tons/ha/year, whereas in 2023, it was 14187.4 tons/ha/year, with the Erosion Hazard Index dominated by the 'Very High' category. For conservation direction, three alternative conservation activities are carried out, namely by vegetative, mechanical, and vegetative-mechanical methods. Based on the results of the analysis, the appropriate conservation direction to reduce the erosion rate is vegetative-mechanical conservation, which can reduce the erosion rate by 66.9% of the existing erosion rate. From the results obtained, it is hoped that new concepts in land conservation that have not yet been implemented in the Way Rarem Sub-watershed can be taken into consideration. Combining two conservation methods, vegetative and mechanical, can be an alternative to controlling erosion that occurs in the Way Rarem Sub-watershed.